FREEDOM OF RELIGION IN JANNAH AL-AT FAL (HEAVEN OF CHILDREN) THE WORKS OF NAJIB MAHFUZ - Munthe, Bermawy (Al-Ulum, 2014)
This study based on the theory of structuralism Robert Stanton, which focuses on the elements of theme in short story Jannah al -At fal (Children of Heaven) by Najib Mahfuz. The result of study was found that the etching of religious freedom to children as a religious education itâs aims to instill competency mastery of basic religious knowledge, attitude differences religious and religious tolerance, interfaith friendship, think and act freely, child relationship and God the Creator, child and the particulars of life and death as well as children and happenings in heaven and hell. This seventh aspect becomes interconnectivity and integrative unity to allow freedom of religion.-----Penelitian ini menggunakan teori strukturalisme Robert Stanton yang menfokuskan pada unsur tema cerita pendek Jannah al-Atfal (Surga Anak-Anak) karya Najib Mahfuz. Penelitian ini menemukan bahwa penanaman kebebasan beragama sebagai pendidikan agama di dalam diri anak-anak kecil bertujuan untuk menanamkan kompetensi penguasaan pengetahuan dasar agama, sikap perbedaan agama dan toleransi beragama, persahabatan lintas agama, berpikir dan bersikap bebas, hubungan anak dan Tuhan Maha Pencipta, anak dan ihwal hidup dan mati serta anak dan ihwal Surga Neraka. Ketujuh aspek ini menjadi kesatuan yang interkonektif dan integratif untuk memungkinkan kebebasan beragama.